Construcción de una noción de aprendizaje para enfrentar la sociedad de la incertidumbre - Carrasco Henríquez, Eduardo; Quintanilla Godoy, Paola; Espinoza Salinas, Ramon; Escobar Riffo, Diego (Universidad de Costa Rica, 2020)
The goal of this article is to show the results of a research process that began in 2018, and that it has the purpose of re-signify the notion of education in the framework of the initial teacher training, considering the new requirements that the 21Th Century society puts to the educational system. These requirements are associated with the description of Bauman about the liquid societies; that's why we worked on the elaboration of a construct for the notion of learning for a society of uncertainty. The study has a qualitative focus, from which to investigate the notion of learning, through a focalized textual corpus, around the context and the use of the word learning. The findings of this investigation show the characterization of learning through the following dimensions, (i) learning as an experience, (ii) learning for a world in constant motion. In summary, the idea is to comprehend the constant transformation that each person has to live to be in a world in constant and interdependent evolution. In this way, the notion of learning for the society of uncertainty, it is expected to develop dialogical thinking, retroactive, recursive, hologrammatic that aboard the condition of autonomy and constant dependence, that assumes the uncertainty.